Predictors of elective pregnancy termination among women diagnosed with HIV during pregnancy in two regions of China, 2004–2010. Issue 10 (2nd November 2012) - Liang, K; Meyers, K; Zeng, W; Gui, X
<x xml:space="preserve">Abstract</x> Please cite this paper as: Liang K, Meyers K, Zeng W, Gui X. Predictors of elective pregnancy termination among women diagnosed with HIV during pregnancy in two regions of China, 2004–2010. BJOG 2013;120:1207–1214. Objective To document the rates of abortion among women diagnosed with HIV during pregnancy in two regions of China, and to investigate the sociodemographic factors associated with women's decisions to terminate their pregnancy. Design Prospective cohort study. Setting Three central Chinese provinces (Hubei, Hebei and Shanxi) and Yining, Xinjiang. Population Women diagnosed with HIV during pregnancy, 2004–2010. Methods Of 798 HIV‐infected pregnant women identified through routine screening of pregnant women via antenatal care between 2004 and 2010, 499 women made decisions about the outcome of pregnancy. Chi‐squared test was used to describe the characteristics of women who chose to terminate their pregnancies. Logistic regression models were used to identify potential predictors for pregnancy outcome for one cohort of women in central China and a second cohort of women in Yining, Xinjiang. Main outcome measures Pregnancy outcome, trends of elective pregnancy termination. Results In the central China cohort, 76 of 161 pregnancies (47.2%) were terminated. In Yining, the proportion was significantly less, at only 61 of 338 (18.0%). Factors associated with pregnancy termination included unmarried marital status, already having one or more children and earlier trimester of pregnancy at the time of diagnosis. Conclusions The rate of pregnancy termination in these cohorts of HIV‐infected women appears to be higher than the rate in the general population of women in China. More work needs to be carried out to decrease the social stigma related to HIV and to convey clear messages about the effectiveness of prevention of mother to child transmission to women and their families. The significantly lower rate of pregnancy termination in Yining relative to central China is probably a result of the cultural and religious reservations towards pregnancy termination. Healthcare workers providing services to HIV‐infected pregnant women need to be sensitive to cultural factors influencing women's decisions with regard to pregnancy termination.